A Study Of Service Quality In Information Technology (IT) Implementations - Chou, Terk Chuan (1995)
This research was conducted to study the service quality in the.. implementation of Information Technology (IT) solutions.The, study Wad intended to measure the service, quality as an "Expectation-Perception Gap" between the IT vendors providing the IT solutions and the customers purchasing and implementing the solutions.